Who is being tested for genital chlamydia in primary care?. Issue 3 (1st June 2003) - Kufeji, O; Slack, R; Cassell, J A; Pugh, S; Hayward, A
Abstract : Objectives: To explore current patterns of testing for genital chlamydial infection in primary care, and to identify practice characteristics influencing testing rates. Method: Aggregate numbers of chlamydia tests and results for each practice in Nottingham Health District were matched to practice characteristics. Age specific testing rates and diagnosed prevalence were calculated, and characteristics of the practice tested for association with chlamydia testing rates. Results: Most tests (63.1%) were performed on women over the age of 25, but the proportion of positive tests was highest in 15–19 year olds (13.3%) followed by 20–24 year olds (8.2%). A higher ratio of GP principals to female practice population was associated with higher testing rates and more chlamydia isolations, but the ratio of female GP principals to patients was associated with higher testing rates only in 20–24 year olds. Diagnosed incidence was greatest in more socioeconomically deprived practice populations, and this was not explained by higher testing rates. Men were rarely tested. Conclusion: Current testing practice in primary care does not reflect the known epidemiology of genital chlamydia infection. Practices with lower doctor-patient ratios do less testing, and measures to enable their active participation in the envisaged screening programme will be important in reaching all at-risk groups.